Anti-fouling fiber structure and producing method thereof

A fiber structure with a polymethacrylate polymer layer on cellulose fibers addresses the issue of contaminant adhesion by providing effective stain resistance and easy removal, enhancing antifouling properties for medical and sanitary uses.

JP2025009339AActive Publication Date: 2025-01-20DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023112271
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

Existing antifouling technologies fail to effectively remove contaminants such as blood, proteins, and oils from fiber surfaces, lacking stain-resistant properties.

Method used

A fiber structure with a polymer layer composed of polymethacrylate grafted onto cellulose fibers, featuring a thickness of 10 to 2,000 nm, a contact angle less than 90°, and a cross-sectional area ratio of 10% or more, allowing easy removal of contaminants with a hydrophilic polymer layer.

Benefits of technology

The fiber structure exhibits excellent antifouling properties, enabling easy removal of adhered contaminants like blood, proteins, and oils through hydrophilic swelling and low friction, suitable for medical and sanitary applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009339000001
    Figure 2025009339000001
  • Figure 2025009339000002
    Figure 2025009339000002
  • Figure 2025009339000003
    Figure 2025009339000003
Patent Text Reader

Abstract

To provide an anti-fouling fiber structure imparted with a function of CPB (concentrated polymer brush) and excellent in anti-fouling property capable of readily removing an adhered contaminant.SOLUTION: An anti-fouling fiber structure comprising a fiber substrate composed of a number of fibers having a hydroxyl group and a polymer layer provided on the surface of the fiber including a grafted polymethacrylate of which one terminal is bonded to the surface of the fiber, wherein the polymethacrylate has a constituent unit derived from a methacrylate monomer such as an alkali metal salt methacrylate, and an average thickness of the polymer layer is 10-2,000 nm, a ratio of the cross-sectional area of polymethacrylate to the surface area of the fiber is 10% or more, the number average molecular weight of the polymethacrylate is 10,000-3,000,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1-1.8, and a contact angle with water at 25°C on the surface of the polymer layer is less than 90°.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a stain-resistant fiber structure and a method for producing the same. [Background technology]

[0002] As a method for modifying a substrate, a method is known in which a polymer having a group at its end that can adsorb or react with the substrate is applied to the substrate to provide a physically or chemically bonded polymer layer on the substrate surface. Also known is a method in which a polymerizable group provided on the substrate surface is used as a starting point to polymerize a monomer to provide a grafted polymer layer from the substrate surface.

[0003] In recent years, research has been conducted on so-called "concentrated polymer brushes," which are densely grafted onto a substrate using the technology of living radical polymerization developed in the 1990s. In these concentrated polymer brushes (hereafter simply referred to as "CPB"), polymer chains formed using vinyl monomers are grafted onto a substrate at a high density with intervals of 1 to 4 nm. In other words, within 1 nm of the substrate surface, 2 At least 0.1 molecular chains of polymer are bonded to each CPB. By modifying the surface of a substrate with this CPB or by swelling the CPB with a good solvent for polymers, the CPB exhibits characteristic functions such as low friction, inhibition of protein adsorption, non-blood clotting, prevention of biofouling, size exclusion, superhydrophilicity, superwater repellency, supercooling properties, and improved tactile properties, and these functions can be imparted to the substrate.

[0004] For example, it has been studied to apply CPB to the surface of substrates such as inorganic materials, plastics, and industrial products, including films (Patent Documents 1 and 2). In addition, a functional fiber fabric has been proposed, which is obtained by applying a liquid composition for polymerization containing multiple monomers to a fiber fabric and polymerizing the composition (Patent Document 3). Furthermore, a functional fabric with a gas deodorizing function has been proposed, in which a radically polymerizable monomer is grafted onto the threads that make up the fabric (Patent Document 4). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 198876 [Patent Document 2] JP 2019-65787 A [Patent Document 3] JP 2006-45686 A [Patent Document 4] JP 2013-155464 A Summary of the Invention [Problem to be solved by the invention]

[0006] Since CPB exhibits extremely low friction, it is expected to contribute to energy conservation in the field of tribology, such as reducing energy loss due to friction, and to address environmental issues such as reducing carbon dioxide emissions. In addition, since CPB exhibits characteristics such as low friction, size exclusion properties, protein adhesion prevention, non-blood coagulation prevention, superhydrophilicity, and superwater repellency, it is expected to provide high-performance medical devices and highly sensitive diagnostic drugs. However, there has not been a fiber structure with excellent stain resistance that can easily remove various contaminants (dirt) including blood, proteins, and animal and vegetable oils and fats, even if they adhere to the fiber.

[0007] The present invention has been made in consideration of the problems of the prior art, and an object of the present invention is to provide a stain-resistant fiber structure having excellent stain-resistant properties, which is endowed with the function of CPB (concentrated polymer brush) and can easily remove attached contaminants. Another object of the present invention is to provide a method for producing the stain-resistant fiber structure. [Means for solving the problem]

[0008] That is, according to the present invention, there is provided the following stain-resistant fiber structure. [1] A soil-resistant fiber structure comprising: a fiber substrate composed of a large number of fibers having hydroxyl groups; and a polymer layer provided on the surface of the fibers, the polymer layer containing polymethacrylate grafted at one end thereof to the surface of the fibers, wherein the polymethacrylate has a constitutional unit derived from at least one methacrylate monomer selected from the group consisting of alkali metal methacrylates, ethylene glycol monoalkyl ether monomethacrylates, polyethylene glycol monoalkyl ether methacrylates, dialkylaminoethyl methacrylates, quaternary ammonium base-containing methacrylates, betaine structure-containing methacrylates, and hydroxyalkyl methacrylates; the average thickness of the polymer layer is 10 to 2,000 nm; the proportion of the cross-sectional area of ​​the polymethacrylate to the surface area of ​​the fibers is 10% or more; the number average molecular weight of the polymethacrylate is 10,000 to 3,000,000 and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1 to 1.8; and the contact angle of the surface of the polymer layer with water at 25°C is less than 90°. [2] The stain-resistant fiber structure according to [1], wherein the fiber is a cellulosic fiber. [3] The stain-resistant fiber structure according to [1] or [2], wherein the contact angle of the surface of the polymer layer with water at 25°C is 60° or less. [4] The stain-resistant fiber structure according to any one of [1] to [3], wherein the methacrylate monomer is polyethylene glycol monoalkyl ether methacrylate. [5] The stain-resistant fiber structure according to any one of [1] to [4], wherein the polymer layer contains an aqueous medium.

[0009] The present invention also provides a method for producing a stain-resistant fiber structure as described below. [6] A method for producing a stain-resistant fiber structure according to any one of [1] to [5] above, comprising the steps of: reacting the fiber substrate with 2-bromoisobutyric acid bromide or 2-bromo-2-methylpropionyloxypropyltrialkylsilane to introduce a 2-bromoisobutyric acid ester group onto the surface of the fiber to obtain an initiator group-containing substrate; and in the presence of the initiator group-containing substrate, surface-initiated living radical polymerization of the methacrylate monomer under a pressure condition of from normal pressure to 1,000 MPa to provide, on the surface of the fiber, the polymer layer containing the polymethacrylate grafted at one end thereof by bonding to the surface of the fiber. Effect of the Invention

[0010] According to the present invention, it is possible to provide a stain-resistant fiber structure having excellent stain resistance, which is endowed with the function of CPB (dense polymer brush) and can easily remove adhering contaminants. In addition, according to the present invention, it is possible to provide a method for producing the above-mentioned stain-resistant fiber structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. One embodiment of the stain-resistant fiber structure of the present invention is a fiber structure comprising a fiber substrate composed of many fibers having hydroxyl groups, and a polymer layer provided on the surface of the fiber, the polymer layer containing polymethacrylate grafted by bonding one end of the fiber to the surface of the fiber. The polymethacrylate has a constitutional unit derived from at least one methacrylate monomer selected from the group consisting of alkali metal methacrylate, ethylene glycol monoalkyl ether monomethacrylate, polyethylene glycol monoalkyl ether methacrylate, dialkylaminoethyl methacrylate, quaternary ammonium base-containing methacrylate, betaine structure-containing methacrylate, and hydroxyalkyl methacrylate. The average thickness of the polymer layer is 10 to 2,000 nm, and the ratio of the cross-sectional area of ​​the polymethacrylate to the surface area of ​​the fiber (exclusive area ratio σ*) is 10% or more. The number average molecular weight of the polymethacrylate is 10,000 to 3,000,000, and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1 to 1.8. The contact angle of the surface of the polymer layer with water at 25° C. is less than 90° C. The stain-resistant fiber structure of this embodiment will be described in detail below.

[0012] (Textile base material) The fiber substrate is a fibrous substrate having a polymer layer, which is CPB, disposed on its surface, and is composed of a large number of fibers having hydroxyl groups. Examples of the fibers include organic fibers and inorganic fibers. Examples of the organic fibers include cellulose fibers, acrylic fibers, polyvinyl alcohol fibers, ethylene vinyl alcohol fibers, and polyolefin fibers. Examples of the inorganic fibers include glass fibers. These fibers and fiber substrates may be surface-treated. In addition, these fibers and fiber substrates may be plasma-treated or the like to impart hydroxyl groups to the fibers.

[0013] The fibers having hydroxyl groups constituting the fiber substrate are preferably cellulose-based fibers. That is, the fiber substrate is preferably a cellulose-based fiber structure composed of a large number of cellulose-based fibers. Since cellulose has hydroxyl groups derived from its structure, it can be used as is without treatment such as plasma treatment, which is preferable from the viewpoint of process simplification and quality uniformity. In addition, since cellulose is a natural material, it is easy to obtain and environmentally degradable, and therefore can contribute to carbon neutrality. Furthermore, since a large number of hydroxyl groups are present on the surface of cellulose, the polymer can be formed more densely.

[0014] The cellulose-based fibers are fibers composed of cellulose or cellulose derivatives, and examples thereof include vegetable fibers, regenerated fibers, and acetates. Specifically, vegetable fibers such as cotton and hemp; regenerated fibers such as rayon, cupra, and lyocell; acetates obtained by partially acetylating cellulose; and the like can be used. In addition, ultrafine fibers such as cellulose fibers, cellulose microfibers, and cellulose nanofibers obtained by defibrating cellulose can also be used.

[0015] The physical properties of the fibers, such as thickness, fineness, length, and specific gravity, are not particularly limited. The average diameter of the fibers is preferably 1 to 100 μm, and more preferably 2 to 50 μm. If the average diameter of the fibers is less than 1 μm, they may be too thin for the polymer layer to be formed, and the performance of the fiber structure may be difficult to maintain. On the other hand, if the average diameter of the fibers exceeds 100 μm, the texture of the fiber structure may be easily impaired. The cross-sectional shape of the fibers may be any of circular, irregular, and irregular shapes.

[0016] Examples of the form of the fiber substrate include woven fabrics, knitted fabrics, and nonwoven fabrics. The structure of the fiber substrate may be woven fabrics such as plain, twill, satin, and oxford, or knitted fabrics such as kanoko, interloop, half, denby, punch, jersey, milling, and smooth. Examples of the nonwoven fabric include dry nonwoven fabrics, wet nonwoven fabrics, spunbond nonwoven fabrics, meltblown nonwoven fabrics, and chemical bond nonwoven fabrics. The mesh size, surface density, and the like of the fiber substrate are not particularly limited. The surface density of the fiber substrate is, for example, 5 to 100 g / cm. 2 It's fine as long as it's to a certain extent.

[0017] (polymer layer) A polymer layer is provided on the surface of a large number of fibers constituting the fiber substrate. This polymer layer contains polymethacrylate grafted at one end thereof to the surface of the fiber. It is preferable that the polymer layer is substantially composed of only polymethacrylate grafted at one end thereof to the surface of the fiber.

[0018] Polymethacrylate is a polymer having a structural unit derived from a methacrylate monomer. The methacrylate monomer is at least one selected from the group consisting of alkali metal methacrylate, ethylene glycol monoalkyl ether monomethacrylate, polyethylene glycol monoalkyl ether methacrylate, dialkylaminoethyl methacrylate, quaternary ammonium base-containing methacrylate, betaine structure-containing methacrylate, and hydroxyalkyl methacrylate. A polymer layer formed of a polymethacrylate having a structural unit derived from these methacrylate monomers can be swollen with various liquid media such as water, organic solvents, and ionic liquids, and has a contact angle of less than 90° with water at 25°C. For this reason, a polymer layer formed of a polymethacrylate having a structural unit derived from a specific methacrylate monomer is provided on the surface of the fiber, and the polymer layer is swollen with a liquid medium as necessary, thereby making it possible to obtain a fiber structure having low friction, abrasion resistance, and other properties, as well as high antifouling properties (the property of easily removing attached dirt).

[0019] Examples of alkali metals constituting the alkali metal methacrylate include lithium, sodium, and potassium. Since the alkali metal methacrylate is a monomer capable of ion dissociation, polymethacrylates having structural units derived from alkali metal methacrylate are highly hydrophilic. Therefore, the polymer layer containing polymethacrylate having structural units derived from alkali metal methacrylate can be swollen by water or an aqueous medium containing water and a water-soluble organic solvent as a good solvent, and can function as a hydrophilic film. In addition, polymethacrylate having structural units derived from alkali metal methacrylate may be formed by polymerizing methacrylic acid whose carboxyl group is protected by a protecting group and then removing the protecting group. Examples of methacrylic acid whose carboxyl group is protected by a protecting group include t-butyl methacrylate, benzyl methacrylate, trimethylsilyl methacrylate, and vinyl ether protected methacrylic acid.

[0020] The number of carbon atoms of the alkyl group constituting the ethylene glycol monoalkyl ether monomethacrylate is preferably 1 to 4. Examples of the ethylene glycol monoalkyl ether monomethacrylate include ethylene glycol monomethyl ether monomethacrylate, ethylene glycol monoethyl ether monomethacrylate, ethylene glycol mono n-propyl ether monomethacrylate, ethylene glycol monoisopropyl ether monomethacrylate, ethylene glycol mono n-butyl ether monomethacrylate, ethylene glycol mono sec-butyl ether monomethacrylate, ethylene glycol monoisobutyl ether monomethacrylate, and ethylene glycol mono tert-butyl ether monomethacrylate. The polymer layer containing the polymethacrylate having a structural unit derived from the ethylene glycol monoalkyl ether monomethacrylate can be swollen in the above-mentioned aqueous medium and exhibits a function as a hydrophilic film. Furthermore, since it exhibits biocompatibility, it exhibits functions that can be applied to the medical field, such as preventing protein adhesion and blood coagulation.

[0021] As the polyethylene glycol monoalkyl ether methacrylate, a monoalkyl ether methacrylate having an ethylene glycol unit with a repeating unit number of 2 to 100 can be used. The number of carbon atoms of the alkyl group constituting the polyethylene glycol monoalkyl ether methacrylate is preferably 1 to 4. Examples of the polyethylene glycol monoalkyl ether methacrylate include polyethylene glycol monomethyl ether methacrylate, polyethylene glycol monoethyl ether methacrylate, polyethylene glycol mono n-propyl ether methacrylate, polyethylene glycol monoisopropyl ether methacrylate, polyethylene glycol mono n-butyl ether methacrylate, polyethylene glycol mono sec-butyl ether methacrylate, polyethylene glycol monoisobutyl ether methacrylate, and polyethylene glycol mono tert-butyl ether methacrylate. The polymer layer containing the polymethacrylate having a constitutional unit derived from the polyethylene glycol monoalkyl ether methacrylate can be swollen in the above-mentioned aqueous medium and exhibits a function as a hydrophilic film. Furthermore, since it exhibits biocompatibility, it exhibits functions applicable to the medical field such as prevention of protein adhesion and blood coagulation.

[0022] The number of carbon atoms of the alkyl group constituting the dialkylaminoethyl methacrylate is preferably 1 or 2. Examples of the dialkylaminoethyl methacrylate include dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate. The polymer layer containing the polymethacrylate having a structural unit derived from the dialkylaminoethyl methacrylate can be swollen with the above-mentioned aqueous medium. In addition, since it is a basic structural unit, it exhibits a function of capturing acidic substances. In addition, after polymerizing these methacrylate monomers, a halide such as benzyl chloride may be reacted to form a quaternary ammonium base. Furthermore, a betaine structure may be formed by reacting with 1,3-propane sultone or the like.

[0023] Examples of quaternary ammonium base-containing methacrylates include methacryloyloxycholine chloride, methacryloyloxycholine bis(trifluoromethanesulfonyl)imide, 2-(methacryloyloxy)-N-benzyl-N,N-dimethylammonium chloride, 2-(methacryloyloxy)-N,N,N-trimethylammonium methylsulfate, N-[2-(methacryloyloxy)ethyl]-N,N-diethylethane-1-ammonium bis(trifluoromethanesulfonyl)imide, and N-[2-(methacryloyloxy)ethyl]-N,N-dimethylbutane-1-ammonium bis(trifluoromethanesulfonyl)imide. The polymer layer containing polymethacrylate having a structural unit derived from a quaternary ammonium base-containing methacrylate can be swollen with the above-mentioned aqueous medium. Furthermore, by swelling with a good solvent, it is possible to make the film superhydrophilic and to develop not only antifouling properties but also antibacterial properties.

[0024] Examples of betaine structure-containing methacrylates include 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate, 4-[[2-((methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonate, 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetate, and 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate. A polymer layer containing a polymethacrylate having a structural unit derived from a betaine structure-containing methacrylate can be swollen with the above-mentioned aqueous medium. Furthermore, by swelling with a good solvent, a superhydrophilic film can be formed, and since it exhibits biocompatibility, it exhibits functions that can be applied to the medical field.

[0025] The number of carbon atoms of the hydroxyalkyl group constituting the hydroxyalkyl methacrylate is preferably 2 to 4. Examples of the hydroxyalkyl methacrylate include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, and 4-hydroxybutyl methacrylate. The polymer layer containing the polymethacrylate having a structural unit derived from the hydroxyalkyl methacrylate can be swollen in the above-mentioned aqueous medium. In addition, the hydrophobicity / hydrophilicity can be controlled or the characteristics can be changed by reacting with a compound that can react with a hydroxyl group.

[0026] The polymethacrylate may be a homopolymer or a copolymer having a random structure or a block structure. The polymethacrylate may further have other structural units other than the structural units derived from the methacrylate monomers described above, as necessary. Examples of monomers constituting other structural units include alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, butyl methacrylate, hexyl methacrylate, and 2-ethylhexyl methacrylate; fluoroalkyl methacrylates such as trifluoromethyl methacrylate and 2,2,3,3,3-pentafluoropropyl methacrylate; and polydimethylsiloxane-containing methacrylates having a polydimethylsiloxane chain of 1 to 100 units.

[0027] The number average molecular weight (Mn) of the polymethacrylate is 10,000 to 3,000,000, preferably 50,000 to 3,000,000, more preferably 100,000 to 1,000,000. If the Mn of the polymethacrylate is less than 10,000, the thickness of the polymer layer is insufficient. On the other hand, it is difficult to polymerize a polymethacrylate having an Mn of more than 3,000,000, and the polymer layer may become excessively thick. In this specification, the number average molecular weight (Mn) and weight average molecular weight (Mw) of the polymer are values ​​calculated as polymethyl methacrylate measured by gel permeation chromatography (GC).

[0028] The molecular weight distribution of the polymethacrylate (PDI=weight average molecular weight (Mw) / number average molecular weight (Mn)) is 1.1 to 1.8, and preferably 1.2 to 1.6. That is, the polymer layer is substantially formed of polymethacrylate having a relatively uniform molecular weight. If the PDI of the polymethacrylate exceeds 1.8, it will contain a large amount of polymer having a molecular weight outside the above-mentioned range, and polymer chains with too large a molecular weight will tend to come out from the surface of the polymer layer, which may prevent the desired performance from being exhibited.

[0029] The average thickness (film thickness) of the polymer layer is 10 to 2,000 nm, preferably 50 to 1,000 nm, and more preferably 100 to 800 nm. The average thickness (film thickness) of the polymer layer in this specification means the average thickness when the polymer layer is dried and not swollen with a liquid medium. The polymer layer constituting the stain-resistant fiber structure of this embodiment is increased in thickness by about 1.5 to 3 times by swelling with a good solvent for the polymethacrylate forming the polymer layer, and properties such as stain resistance, low friction, and abrasion resistance are improved. If the average thickness of the polymer layer is less than 10 nm, the swelling amount is small even when the polymer layer is swollen with a liquid medium, and the effect of improving the properties is insufficient. On the other hand, if the average thickness of the polymer layer is more than 2,000 nm, the texture of the fiber structure is likely to change depending on the properties of the polymethacrylate, and the fiber structure may become sticky or hard.

[0030] The ratio of the cross-sectional area of ​​polymethacrylate to the surface area of ​​the many fibers constituting the fiber substrate (hereinafter also referred to as "exclusive area ratio σ*") is 10% or more, preferably 20% or more, and more preferably 30% or more. By forming a polymer layer by densely grafting polymethacrylate so that the exclusive area ratio σ* is 10% or more, properties such as antifouling, low friction, and abrasion resistance can be exhibited. The theoretical upper limit (closest packing) of the exclusive area ratio σ* is 100%. The exclusive area ratio σ* is, for example, 70% or less, preferably 60% or less.

[0031] The exclusive area ratio σ* is calculated by the following formula (1)2 )" according to the following formula (2). σ = dLNAMn (1) σ* = σS × 100 (2) d: density of the polymer (polymethacrylate) L: thickness of the polymer layer NA: Avogadro's number Mn: Number average molecular weight of the polymer (polymethacrylate) S: Cross-sectional area of ​​the polymer (polymethacrylate)

[0032] The thickness of the polymer layer can be measured by a conventional method using, for example, an ellipsometer, an electron microscope, an atomic force microscope, etc. The density of the polymer can be measured by a value described in a conventional document or a value measured by a method described in JIS K 7112:1999, etc. The cross-sectional area of ​​the polymer can be determined from the repeating unit length in the fully stretched form of the polymer and the bulk density of the polymer.

[0033] The contact angle of the surface of the polymer layer with water at 25°C is less than 90°, preferably 60° or less, more preferably 30° or less. The polymer layer is highly hydrophilic and easily absorbs water and swells, so that attached dirt is quickly removed. The contact angle with water at 25°C is a physical property value measured using a contact angle meter or the like in accordance with the sessile drop method of JIS R 3257:1999. As the contact angle meter, for example, the product name "LSE-ME" series (manufactured by Nick Co., Ltd.); the product series "DropMaster" series (manufactured by Kyowa Interface Science Co., Ltd.) can be used. In addition, a silicon substrate is coexisted when the polymer layer is formed (at the time of polymerization), and the contact angle of the surface of the polymer layer formed on the surface of the silicon substrate is measured. The value of the contact angle obtained can be estimated as the contact angle of water on the surface of the polymer layer of the soil-resistant fiber structure.

[0034] It is preferable that the polymer layer contains an aqueous medium. That is, it is preferable that the polymer layer contains an aqueous medium and is swollen. The aqueous medium is water or a mixed solvent of water and a water-soluble organic solvent. Examples of the water-soluble organic solvent include alcohol-based solvents such as methanol, ethanol, ethylene glycol, propylene glycol, and glycerin; organic polar amide-based solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-methylcaprolactam; ether compound solvents such as tetrahydrofuran and dioxane; ketone compound solvents such as acetone and methyl ethyl ketone; nitrile compound solvents such as acetonitrile and propionitrile; ionic liquids; and solvents in which inorganic salts such as sodium chloride, calcium chloride, ammonium chloride, sodium acetate, and sodium hydrogen carbonate are dissolved.

[0035] Since the stain-resistant fiber structure of the present embodiment has a hydrophilic polymer layer, even if dirt (contaminants) are attached, the attached contaminants can be easily removed by washing with water or the like. Examples of contaminants include water-soluble dirt such as salt, sugar, and blood; poorly soluble dirt such as pigments and denatured proteins; strongly polar oily dirt such as fatty acids; medium polar oily dirt such as animal and vegetable oils and fats; non-polar oily dirt such as mineral oil; hydrophilic solid dirt such as mud, iron oxide, and calcium carbonate; and hydrophobic solid dirt such as carbon black. In particular, contaminants such as blood, protein, and animal and vegetable oils and fats can be easily removed. Examples of proteins include simple proteins such as albumin, globumin, glutelin, keratin, collagen, and fibroin; complex proteins such as sugar, phosphorus, pigments, and nuclear proteins; and the like. Examples of animal and vegetable fats and oils include drying oils such as perilla oil and linseed oil, which have an iodine value of 130 or more; semi-drying oils such as sesame oil and soybean oil, which have an iodine value of 100 to 130; and non-drying oils such as olive oil and castor oil, which have an iodine value of 100 or less.

[0036] Stain resistance is generally divided into three types: SG, SR, and SGR. "High (excellent) SG" means that hydrophilic and lipophilic stains are difficult to adhere to the fiber due to the application of a water- and oil-repellent treatment such as a fluorine-based resin treatment. "High (excellent) SR" means that stains are easily removed by washing due to the application of a hydrophilic treatment to the fiber surface. "High (excellent) SGR" means that stains are difficult to adhere to and easy to remove. The stain-resistant fiber structure of this embodiment mainly has "high (excellent) SR". That is, even if contaminants adhere to the surface of the stain-resistant fiber structure of this embodiment, the contaminants can be easily removed by immersing the fiber structure in an aqueous medium or wiping it off with a cloth containing an aqueous medium.

[0037] Since the stain-resistant fiber structure of this embodiment has a polymer layer exhibiting characteristic properties, it is expected to be used in a variety of fields, such as medical and sanitary applications, daily necessities, clothing, and interior and bedding applications.

[0038] <Method of manufacturing stain-resistant fiber structure> One embodiment of the method for producing a soil-resistant fiber structure of the present invention is the method for producing the soil-resistant fiber structure described above, and includes a step of obtaining an initiator group-containing substrate (step (1)) and a step of providing a polymer layer on the surface of the fiber (step (2)). In step (1), 2-bromoisobutyric acid bromide or 2-bromo-2-methylpropionyloxypropyltrialkylsilane is reacted with the fiber substrate to introduce 2-bromoisobutyric acid ester groups onto the fiber surface to obtain an initiator group-containing substrate. In step (2), in the presence of the obtained initiator group-containing substrate, a methacrylate monomer is subjected to surface-initiated living radical polymerization under pressure conditions of normal pressure to 1,000 MPa. As a result, a polymer layer containing polymethacrylate grafted by bonding one end to the fiber surface is provided on the fiber surface.

[0039] By reacting 2-bromoisobutyric acid bromide or 2-bromo-2-methylpropionyloxypropyltrialkylsilane with a fiber substrate, a 2-bromoisobutyric acid ester group, which is a polymerization initiation group, is introduced onto the surface of the fiber constituting the fiber substrate, and an initiator group-containing substrate can be obtained. In particular, when the fiber is a cellulose-based fiber, an initiator group-containing substrate having a high concentration of polymerization initiation groups introduced onto its surface can be obtained.

[0040] A method for reacting 2-bromoisobutyric acid bromide with a fiber substrate can be immersed in 2-bromoisobutyric acid bromide diluted with an organic solvent. A base such as pyridine may be present in the reaction solution. Alternatively, a base may be dissolved in the organic solvent, the fiber substrate may be immersed in the organic solvent, and 2-bromoisobutyric acid bromide may be dripped in to cause the reaction. Furthermore, the vapor of 2-bromoisobutyric acid bromide may be sprayed on the fiber substrate.

[0041] In addition, when a fiber substrate made of glass fiber or the like is used, it is preferable to react with 2-bromo-2-methylpropionyloxypropyl trialkylsilane. By reacting with 2-bromo-2-methylpropionyloxypropyl trialkylsilane, a polymerization initiator group can be introduced to the surface of the fiber by dealcoholization and dehydration. As the 2-bromo-2-methylpropionyloxypropyl trialkylsilane, 2-bromo-2-methylpropionyloxypropyl trimethoxysilane, 2-bromo-2-methylpropionyloxypropyl triethoxysilane, and 2-bromo-2-methylpropionyloxypropyl dimethoxyethoxysilane can be used.

[0042] As a method for reacting 2-bromo-2-methylpropionyloxypropyltrialkylsilane with a fiber substrate, a method of spraying 2-bromo-2-methylpropionyloxypropyltrialkylsilane onto the fiber substrate using a sprayer and then drying the same can be mentioned. Alternatively, the fiber substrate may be immersed in a reaction solution in which 2-bromo-2-methylpropionyloxypropyltrialkylsilane is dissolved in a solvent such as ethanol. This reaction solution may be made basic by adding an aqueous ammonia solution, or may be made acidic by adding acetic acid or hydrochloric acid.

[0043] In the presence of an initiator-containing substrate, a surface-initiated living radical polymerization of a methacrylate monomer is performed to provide a polymer layer containing a polymethacrylate grafted at one end to the surface of the fiber on the surface of the fiber, thereby obtaining the desired antifouling fiber structure. Examples of surface-initiated living radical polymerization include atom transfer radical polymerization (ATRP method) performed by oxidation-reduction using a metal complex of copper or ruthenium as a catalyst; reversible catalyst-mediated polymerization (halogen exchange RCMP method) in which halogen exchange is performed using a quaternary ammonium iodide salt or the like, and polymerization proceeds with the quaternary ammonium salt as a catalyst; and the like. In other words, by performing living radical polymerization starting from the polymerization initiator group introduced on the surface of the fiber, a polymer layer with dense grafting of the polymer can be formed on the surface of the fiber.

[0044] In the ATRP method, a monomer is polymerized using a metal complex. As the metal complex, a metal complex having an element of Groups 7 to 11 of the periodic table as a central metal is used. Specifically, a metal complex containing monovalent copper, divalent copper, divalent ruthenium, divalent iron, or divalent nickel can be mentioned. Among them, it is preferable to use a metal complex containing monovalent copper or divalent copper, which is inexpensive and easily available. More specifically, copper(I) chloride, copper(II) chloride, copper(I) bromide, copper(II) bromide, copper(I) iodide, and copper(II) iodide can be mentioned. When these copper metal complexes are used as polymerization catalysts, a polyamine that forms a complex is used as a ligand. Examples of the ligand include 2,2-bipyridine, dinonyl bipyridine, phenanthroline, tridimethylaminoethylamine, pentamethyldiethylenetriamine, tris[2-(dimethylamino)ethyl]amine, tris(2-picolyl)amine, and N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine, etc. The amount of the metal catalyst relative to 100 parts by mass of the monomer is preferably 0.001 to 0.1 parts by mass.

[0045] In order to prevent the deactivation of the catalyst during polymerization, a reducing agent may be used. Examples of the reducing agent include tin dilaurate and ascorbic acid. In addition, an azo-based polymerization initiator such as azobisisobutyronitrile may be added to promote polymerization.

[0046] The ATRP method may be bulk polymerization or solution polymerization using an organic solvent or the like. Examples of the organic solvent include hydrocarbon solvents, ester solvents, glycol solvents, ether solvents, amide solvents, alcohol solvents, sulfoxide solvents, urea solvents, and ionic liquids. Among them, it is preferable to use a solvent with high polarity such as an ionic liquid, since it can improve the polymerization rate and increase the thickness of the polymer layer. Examples of the ionic liquid include ionic liquids such as quaternary ammonium salts, imidazolium salts, pyridinium salts, quaternary phosphonium salts, and guanidinium salts.

[0047] In the halogen exchange RCMP method, salt compounds such as quaternary ammonium iodide salts, phosphonium iodide salts, and alkali metal iodide salts are used. The halogen exchange RCMP method is a method using commercially available organic materials and inexpensive inorganic salts, so it is preferable from the viewpoint of reducing costs and environmental burden, and is also preferable because it does not require metal removal and can simplify the process. In the halogen exchange RCMP method, the polymerization initiator group is halogen-exchanged with the salt compound to form a 2-iodoisobutyric acid ester group. Next, the salt compound acts as a catalyst to turn iodine into a radical and release it, and then a monomer is inserted into the carbon radical to polymerize. The released iodine immediately binds to prevent a termination reaction, and the polymerization proceeds in a living manner.

[0048] Among the salt compounds, examples of quaternary ammonium iodide salts include benzyltetrabutylammonium iodide, tetrabutylammonium iodide, tetraoctylammonium iodide, dedocyltrimethylammonium iodide, octadecyltrimethylammonium iodide, trioctadecylmethylammonium iodide, etc. From the viewpoint of increasing the activity and obtaining a thicker polymer with a high molecular weight, the amount of the salt compound relative to the polymerization initiator group is preferably at least an equimolar amount, more preferably at least 10 times the molar amount, and particularly preferably at least 100 times the molar amount.

[0049] The temperature during polymerization is preferably 60° C. or higher. The polymerization is preferably carried out in the presence of an organic solvent. The organic solvent is preferably an organic solvent that dissolves salts, and it is preferable to use an organic solvent having high polarity, such as an alcohol, glycol, amide, urea, sulfoxide, or ionic liquid.

[0050] In step (2), the methacrylate monomer is subjected to surface-initiated living radical polymerization under pressure conditions of normal pressure to 1,000 MPa, preferably 10 to 1,000 MPa. By transmitting pressure to the inside of the polymerization vessel through a liquid medium such as water, the termination reaction is suppressed, and polymethacrylate with a higher molecular weight can be formed. When the molecular weight of the polymethacrylate increases, the thickness of the polymer layer formed increases. By forming a thicker polymer layer, it is possible to impart unprecedented properties to the fiber substrate.

[0051] The polymerization may be carried out in a polymerization vessel. As the polymerization vessel, it is preferable to use a sealable vessel that can withstand high pressure. As the polymerization vessel, a polyethylene bottle, a PET bottle, a retort pouch, a blister container, or the like can be used. In addition, in consideration of polymerization under warming or heating conditions, it is preferable to use a polymerization vessel made of a material having heat resistance. Furthermore, it is preferable to use a polymerization vessel made of a material having properties such as chemical resistance and solvent resistance. Examples of such materials include polyolefin, fluororesin, polyester, polyamide, and engineering plastics.

[0052] When the polymerization solution is charged into the polymerization vessel, it is preferable to prevent a large space from being formed, that is, to prevent gas from getting into the polymerization vessel. Specifically, it is preferable to charge the polymerization solution to 90% or more of the vessel volume.

[0053] The molecular weight of the polymer (polymethacrylate) forming the polymer layer can be measured by analyzing the polymer cut out from the soil-resistant fiber structure by a method such as hydrolysis. In addition, a surface-initiated living radical polymerization is carried out in a state where a compound (free initiator compound) such as ethyl 2-bromoisobutyrate having a structure similar to that of the polymerization initiator group is added to the polymerization system, and the molecular weight of the free polymer generated by polymerization proceeding from the initiator group of the free initiator compound is measured. The molecular weight of the free polymer measured in this way can be estimated as the molecular weight of the polymer forming the polymer layer.

[0054] The content of the free initiator compound in the polymerization system is preferably 0.01% by mass or less, more preferably 0.001% by mass or less. If the content of the free initiator compound is too high, the viscosity of the polymerization system may increase too much. This may make it difficult to remove the obtained stain-resistant fiber structure or take a long time to wash it. EXAMPLES

[0055] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0056] <Manufacturing of fiber structures> (Example 1 and Comparative Example 1) A4 size nonwoven fabric (100% cotton) was prepared as a fiber substrate, ultrasonically cleaned with methyl ethyl ketone (MEK), tetrahydrofuran (THF), and methanol, and then air-dried. The fiber substrate was immersed in a mixed solution of toluene / 2-bromoisobutyric acid bromide / pyridine (mass ratio = 85 / 10 / 5) for 1 hour to react, introducing 2-bromoisobutyric acid ester groups onto the fiber surface to obtain an initiator group-containing substrate. The obtained initiator group-containing substrate was washed with methanol and then air-dried. When infrared absorption was measured using an infrared spectrophotometer, it was found that the 1,720 cm -1 Absorption was confirmed, confirming that the polymerization initiation group, 2-bromoisobutyric acid ester group, had been introduced.

[0057] 0.08 parts of copper bromide, 0.004 parts of copper bromide, 0.5 parts of dinonyl bipyridine, 40 parts of polyethylene glycol monomethyl ether methacrylate (trade name "PME-400", NOF Corp.), 59 parts of anisole, and 1 part of anisole solution of 2-ethyl bromoisobutyrate (EBIB) (EBIB concentration: 0.0008%) were put into a glass sample bottle and homogenized to obtain a brown polymerization solution. The initiator-containing substrate and silicon substrate (1 cm x 2 cm) were placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device (trade name "Marugoto Extract", Toyo Koatsu Co., Ltd.), and polymerization was performed for 1 hour under conditions of 60°C and 400 MPa. A viscous polymer solution was formed in the aluminum pouch. A portion of the polymer solution was sampled, and the molecular weight of the polymer formed was measured by gel permeation chromatography (GPC) using dimethylformamide (DMF) as a developing solvent. As a result, the number average molecular weight (Mn) of the polymer was 2,860,000 and the molecular weight distribution (PDI) was 1.17.

[0058] The contents of the aluminum pouch were removed and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the fibers were dried by blowing air to obtain a fiber structure (Example 1) and a treated silicon substrate. The obtained fiber structure was observed with a field emission scanning electron microscope (FE-SEM), and the thickness of the formed polymer layer was measured at three arbitrary points, and the average value was taken as the "thickness of the polymer layer". As a result, the thickness of the polymer layer was 515 nm. In addition, the ratio of the cross-sectional area of ​​the polymethacrylate to the surface area of ​​the fiber (exclusive area ratio σ*), calculated from the above-mentioned formulas (1) and (2), was 36%. An untreated nonwoven fabric (fiber substrate) was used as Comparative Example 1.

[0059] The polymer layer formed on the treated silicon substrate had a thickness of 520 nm and an occupied area of ​​36%. The contact angle of the surface of the polymer layer formed on the treated silicon substrate with water at 25°C was measured using a contact angle meter (product name "DropMaster100", manufactured by Kyowa Interface Science Co., Ltd.) to be 35°, confirming that the polymer layer was hydrophilic. The treated silicon substrate was immersed in water at room temperature (25°C) and atmospheric pressure. The thickness of the polymer layer was then measured using an atomic force microscope (AFM) to be 1,200 nm, confirming that the polymer layer was swelled.

[0060] (Examples 2 to 7) Fiber structures (Examples 2 to 7) were obtained in the same manner as in Example 1 above, except that the conditions were as shown in Table 1. The physical properties of the obtained fiber structures are shown in Table 1. The meanings of the abbreviations in Table 1 are as follows. ·DMAEMA: Dimethylaminoethyl methacrylate ·HEMA: Hydroxyethyl methacrylate MMA: Methyl methacrylate ·DEGBMA: Diethylene glycol monobutyl ether methacrylate

[0061] TIFF2025009339000001.tif102170

[0062] Comparative Example 2 A4 size nonwoven fabric (80% rayon, 20% PP) was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator-containing substrate. 0.08 parts of copper bromide, 0.004 parts of copper bromide, 0.5 parts of dinonyl bipyridine, 40 parts of tert-butyl methacrylate (t-BuMA), 59 parts of anisole, and 1 part of an anisole solution of EBIB (EBIB concentration: 0.0008%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator-containing substrate and silicon substrate (1 cm x 2 cm) were placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device and polymerized for 4 hours under conditions of 60 °C and 100 MPa. A viscous polymer solution was produced in the aluminum pouch. The Mn of the produced polymer was 210,000, and the PDI was 1.19. The contents of the aluminum pouch were removed and immersed in THF for 12 hours. After ultrasonic cleaning with methanol (MeOH), the fiber structure was dried by blowing air to obtain a fiber structure (Comparative Example 2). The polymer layer of the obtained fiber structure had a film thickness of 182 nm and an area ratio σ* of 42%. In addition, the contact angle of the surface of the polymer layer with water was 98°.

[0063] Example 8 Five parts of p-toluenesulfonic acid and 95 parts of DMF were placed in a flask, and the p-toluenesulfonic acid was dissolved. The initiator group-containing base material and silicon substrate obtained in Comparative Example 2 were immersed in the solution, heated to 80°C, and reacted for 10 hours to deprotect the t-butyl ester group. After cooling, the contents were removed, thoroughly washed with MeOH and pure water, and then dried in a blower dryer at 80°C to obtain a fiber structure. The surface IR was measured, and a 1,700 cm IR due to the carboxyl group was obtained. -1 Absorption was confirmed near the surface of the substrate. A 5% aqueous solution of sodium hydroxide was placed in a beaker, and the fiber structure and the treated silicon substrate were immersed in the solution. After thorough washing with pure water, the fiber structure was dried in a blower dryer at 80°C to obtain a fiber structure (Example 8).

[0064] Example 9 12.2 parts of benzyl chloride (BzCl) and 100 parts of acetone were placed in a sample tube to dissolve the benzyl chloride. The precursor of the initiator-containing base material obtained in Example 4 (precursor monomer: dimethylaminoethyl methacrylate (DMAEMA)) and a silicon substrate were immersed and reacted at room temperature for 12 hours to convert the polymer into a quaternary ammonium salt. The contents were removed, thoroughly washed with MeOH and pure water, and then dried in a blower dryer at 80°C to obtain a fiber structure (Example 9). The surface IR was measured, and a 780 cm -1 The thickness of the polymer layer of the resulting fiber structure was 840 nm.

[0065] Example 10 12.2 parts of 1,3-propane sultone, 20 parts of acetonitrile, and 80 parts of water were placed in a sample tube to dissolve the 1,3-propane sultone. The precursor of the initiator-containing base material obtained in Example 4 (precursor monomer: DMAEMA) and a silicon substrate were immersed and reacted at 60°C for 12 hours to zwitterionize the polymer. After cooling, the contents were removed, thoroughly washed with MeOH and pure water, and then dried in a blower dryer at 80°C to obtain a fiber structure (Example 10). The surface IR was measured, and a 1,030 cm IR due to the sulfonyl group was obtained. -1 The thickness of the polymer layer of the resulting fiber structure was 920 nm.

[0066] The results of Examples 8 to 10 are shown in Table 2.

[0067] TIFF2025009339000002.tif115170

[0068] (Comparative Examples 3 and 4) Fiber structures (Comparative Examples 3 and 4) were obtained in the same manner as in Comparative Example 2, except that the conditions were as shown in Table 3. The physical properties of the obtained fiber structures are shown in Table 3. In Table 3, "LMA" means "lauryl methacrylate" and "TFEMA" means "2,2,2-trifluoroethyl methacrylate".

[0069] TIFF2025009339000003.tif116170

[0070] Comparative Example 5 A4-sized nonwoven fabric (100% cotton) was prepared as a fiber substrate, ultrasonically cleaned with MEK, THF, and MeOH, and then dried by blowing air. The fiber substrate was immersed in a mixed solution of toluene / methacrylic acid bromide / pyridine (mass ratio = 85 / 10 / 5) for 1 hour to react, and methacrylic acid ester groups were introduced onto the fiber surface to obtain an initiator group-containing substrate. The obtained initiator group-containing substrate was washed with methanol and then dried by blowing air. When infrared absorption was measured using an infrared spectrophotometer, it was found that the 1,720 cm -1 Absorption of the methacrylic acid ester group, which is a polymerization initiating group, was confirmed, and it was confirmed that the methacrylic acid ester group was introduced.

[0071] The initiator-containing substrate, silicon substrate (1 cm x 2 cm), and 100 parts of PME-400 were placed in a flask. After heating to 65°C and bubbling with nitrogen for 1 hour, 0.1 parts of 2,2-azobis(2-methylpropionitrile) (AIBN) were added and reacted for 24 hours. A viscous polymer solution was produced in the flask. The Mn of the produced polymer was 450,000 and the PDI was 2.50. The contents of the flask were taken out, immersed in THF for 12 hours, and then dried by blowing air to obtain a fiber structure (Comparative Example 5). The film thickness of the polymer layer of the obtained fiber structure was 13 nm, and the occupied area ratio σ* was 6%. In addition, the contact angle of the surface of the polymer layer with water was 34°.

[0072] Comparative Example 6 A4 size nonwoven fabric (100% cotton) was prepared as a fiber substrate, ultrasonically cleaned with MEK, THF, and MeOH, and then air-dried. 90 parts of PME-400 and 10 parts of 2-isocyanatoethyl methacrylate (MOI) were placed in a flask, and nitrogen was bubbled at 65°C for 1 hour, after which 0.1 parts of AIBN was added and reacted for 24 hours. A viscous polymer solution was produced in the flask. The Mn of the produced polymer was 350,000 and the PDI was 2.34. The fiber substrate was immersed in the polymer solution and reacted at 80°C for 1 hour. The contents of the flask were removed and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the fiber substrate was air-dried to obtain a fiber structure (Comparative Example 6). The film thickness of the polymer layer of the obtained fiber structure was 11 nm, and the occupied area ratio σ* was 6%. In addition, the contact angle of the surface of the polymer layer with water was 35°.

[0073] <Evaluation> (Stain removal (1)) First, a "stain resistance test against practical everyday stains (BOKEN standard BQE A 039)" was conducted according to the following procedure. [1] Test pieces obtained by cutting the fiber structures (Example 1, Example 2, and Comparative Example 1) to an appropriate size were placed on a smooth glass plate. [2] 0.2 g of chili oil was dropped onto the test piece and left for 60 seconds. [3] The test pieces were immersed in water and the release behavior of the chili oil was observed.

[0074] Significant improvements in SR properties were observed in the fiber structures of Examples 1 and 2. In contrast, the fiber structure of Comparative Example 1 did not exhibit a stain-resistant effect and the adsorption of chili oil to the fiber was strong.

[0075] Next, the stain removal property was evaluated using a contaminant. First, 61.9 parts of olive oil (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 38.0 parts of oleic acid (manufactured by Sigma-Aldrich Japan Co., Ltd.), and 0.1 parts of oil red (manufactured by Sigma-Aldrich Japan Co., Ltd.) were mixed to prepare a contaminant. Then, using the prepared contaminant, a test was performed according to the following procedure. [1] A test specimen was prepared by cutting the fiber structure to a size of 8 cm x 8 cm and placed on a smooth glass plate. [2] 0.1 mL of the contaminant was dropped from a height of 10 cm using a micropipette and left for 60 seconds. [3] After placing the filter paper on the surface and absorbing the dirt under its own weight, the filter paper was moved and the dirt was again absorbed with the uncontaminated part of the filter paper. This process was repeated until the filter paper no longer absorbed the dirt. If the filter paper did not touch the contaminated part, both ends of the filter paper were held and the dirt was absorbed by contacting the filter paper with the dirt while applying as little weight as possible. [4] The contaminated test specimens were immersed in pure water for one hour within one hour of application of the contaminant. [5] After the test pieces were dried, they were compared with the test pieces before the contaminants were dropped, and the degree of remaining dirt was evaluated in the order of "x", "△", "◯", and "◎". The results are shown in Table 4.

[0076] TIFF2025009339000004.tif56170

[0077] (Stain removal (2)) Artificial blood (defibroinized horse blood (Japan Biotest Laboratory) with viscosity adjusted to 8.0 mPa·s) was prepared. Using the prepared artificial blood, the test was carried out according to the following procedure. [1] Test pieces obtained by cutting the fiber structures (Example 1, Comparative Example 1, Comparative Example 5, and Comparative Example 6) to an appropriate size were placed on a smooth glass plate. [2] 0.2 g of artificial blood was dropped onto the test piece and left for 60 seconds. [3] After placing the filter paper on the surface and absorbing the dirt under its own weight, the filter paper was moved and the dirt was again absorbed with the uncontaminated part of the filter paper. This process was repeated until the filter paper no longer absorbed the dirt. If the filter paper did not touch the contaminated part, both ends of the filter paper were held and the dirt was absorbed by contacting the filter paper with the dirt while applying as little weight as possible. [4] The contaminated test piece was immersed in pure water for 1 hour within 1 hour after the artificial blood was dropped. The test piece was then visually inspected, and those where the blood stains were removed were rated as "○", and those where they were not removed were rated as "×". The results are shown in Table 5.

[0078] (Protein stains after cleaning) A protein solution was prepared by dissolving 3 mg of bovine serum albumin (BSA) in 1 mL of purified water. The prepared protein solution was used to carry out the test according to the following procedure. [1] Test pieces obtained by cutting the fiber structures (Example 1, Comparative Example 1, Comparative Example 5, and Comparative Example 6) to an appropriate size were placed on a smooth glass plate. [2] 0.1 mL of the protein solution was dropped onto the test piece and left for 60 seconds. [3] After placing the filter paper on the surface and absorbing the dirt under its own weight, the filter paper was moved and the dirt was again absorbed with the uncontaminated part of the filter paper. This process was repeated until the filter paper no longer absorbed the dirt. If the filter paper did not touch the contaminated part, both ends of the filter paper were held and the dirt was absorbed by contacting the filter paper with the dirt while applying as little weight as possible. [4] The contaminated test specimen was immersed in pure water for one hour within one hour after the protein solution was applied. [5] A yellow detection solution was prepared by mixing 250 mL of tetrabromophenol blue (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 650 mL of ethanol, 100 mL of 1 mol / L citric acid, and 150 mL of glycerin. After dropping 0.2 mL of the prepared detection solution onto the test piece, the test piece was visually observed, and those that did not change color were evaluated as "negative," and those that changed color to green were evaluated as "positive." The results are shown in Table 5.

[0079] TIFF2025009339000005.tif70170 [Industrial Applicability]

[0080] The stain-resistant fiber structure of the present invention is expected to be used in applications that utilize the low friction inherent in the CPB material, as well as the inhibition of protein adsorption, non-blood coagulation properties, and anti-biofouling properties, etc. In particular, it is useful as a material for medical devices, diagnostic drugs, sanitary products, daily materials, clothing, agricultural materials, and filtration / adsorption applications.

Claims

1. A fiber base material composed of a large number of fibers having hydroxyl groups; a polymer layer disposed on the surface of the fiber, the polymer layer comprising polymethacrylate grafted at one end thereof to be bonded to the surface of the fiber; the polymethacrylate has a constituent unit derived from at least one methacrylate monomer selected from the group consisting of alkali metal methacrylates, ethylene glycol monoalkyl ether monomethacrylates, polyethylene glycol monoalkyl ether methacrylates, dialkylaminoethyl methacrylates, quaternary ammonium base-containing methacrylates, betaine structure-containing methacrylates, and hydroxyalkyl methacrylates; The average thickness of the polymer layer is 10 to 2,000 nm; The ratio of the cross-sectional area of ​​the polymethacrylate to the surface area of ​​the fiber is 10% or more; The polymethacrylate has a number average molecular weight of 10,000 to 3,000,000 and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.1 to 1.8; A stain-resistant fiber structure, wherein the contact angle of the surface of the polymer layer with water at 25° C. is less than 90°.

2. 2. The stain resistant fiber structure according to claim 1, wherein the fiber is a cellulosic fiber.

3. 2. The stain-resistant fiber structure according to claim 1, wherein the contact angle of the surface of the polymer layer with water at 25° C. is 60° or less.

4. 2. The stain resistant fiber structure according to claim 1, wherein the methacrylate monomer is polyethylene glycol monoalkyl ether methacrylate.

5. The stain resistant fiber structure according to claim 1 , wherein the polymer layer contains an aqueous medium.

6. A method for producing the stain-resistant fiber structure according to any one of claims 1 to 5, comprising the steps of: a step of reacting the fiber substrate with 2-bromoisobutyric acid bromide or 2-bromo-2-methylpropionyloxypropyltrialkylsilane to introduce 2-bromoisobutyric acid ester groups onto the surface of the fiber to obtain an initiator group-containing substrate; a step of subjecting the methacrylate monomer to surface-initiated living radical polymerization under a pressure condition of normal pressure to 1,000 MPa in the presence of the initiator group-containing substrate to provide the polymer layer on the surface of the fiber, the polymer layer including the polymethacrylate grafted at one end thereof by being bound to the surface of the fiber; A method for producing a stain-resistant fiber structure having the above structure.

Citation Information

Patent Citations

  • Adsorbent with enhanced ratio of polymer brush and method for removing useful or harmful material using the adsorbent

    JP2017164698A

  • Antifouling fabric and method for manufacturing the same

    JP2020133018A

  • Composition, cured film, laminate, vessel, underwater structure, medical device, and microchannel chip

    JP2021123712A

  • Virus inactivation structure

    JP2022157406A

  • Surface modified film, method for producing surface modified film, and surface modified substrate

    JP2023012123A